A new and reliable intelligent model for deployment of sensor nodes for IoT applications. (July 2022) - Dash, Ranjan Kumar; Cengiz, Korhan; Alshehri, Yasser Ali; Alnazzawi, Noha
Abstract: To ensure reliable Internet of Things (IoT) applications, this study provides a new intelligent deployment technique for sensor nodes. The proposed intelligent deployment technique places sensor nodes in appropriate locations to achieve high levels of connectivity and, as a result, boost the WSN's overall reliability. To generate optimal sensor node coordinate positions, a modified version of the Expectation–Maximization method is utilized as a machine learning technique. Following that, each node's neighbours are determined, and links between them are built using the K-Nearest neighbour algorithm. Then, to assess the reliability of WSN, a novel algorithm is proposed. The proposed algorithms are all well-illustrated with appropriate examples. When the algorithms provided in this research are compared to certain existing methods in terms of node positioning accuracy (10%), network connectivity (10%), and estimated dependability values (5%), it is clear that the suggested strategy outperforms them in every way. Graphical abstract: Highlights: Using Modified EM algorithm to generate optimal positions of sensors of WSNs. A new algorithm based on node disjoint minimal path to evaluate reliability of WSNs. Positioning accuracy, connectivity, and reliability were increased significantly. Assess the impact of transmission range and time on values of reliability of WSNs.